PERBANDINGAN STRUKTUR NARATIF PENDERITAAN PEREMPUAN DALAM CERPEN GADIS KOREK API DAN PESTA TUBUH - Maulidia, Zulia Khikmatul; Afdholy, Nadya; Purnomo, Antonius Rahmat Pujo; Bramantio (SEBASA Jurnal Pendidikan Bahasa dan Sastra, 2025)
The aim of this study is to analyze the narrative structure in two short stories, Gadis Korek Api by Djenar Maesa Ayu and Pesta Tubuh by Oka Rusmini, using Genette’s narratology theory, particularly focusing on the aspects of order and frequency. The analysis shows that both stories employ the technique of analepsis, which is the insertion of past events into the present narrative in a non-chronological manner. In terms of frequency, Gadis Korek Api features anaphoric and iterative frequency, while Pesta Tubuh contains anaphoric and repetitive frequency. Both short stories present a non-linear narrative structure that emphasizes the recurring trauma and experiences of the main characters. The past is gradually revealed as part of a living narrative that shapes the characters’ identities. In terms of frequency, some events shows that the content of the fairy tale read or recited by the main character functions as a reinforcement and solace for the woman's suffering. This study demonstrates that the application of Genette’s narratology yields unique findings, particularly in identifying patterns of analepsis and narrative frequency in these two short stories. Thus, this research not only enriches the reading of both stories but also underscores the importance of structural approaches in modern narrative studies.